2011
DOI: 10.1152/physiolgenomics.00179.2010
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in hepatic one-carbon metabolism and related pathways following a high-fat dietary intervention

Abstract: Obesity frequently leads to insulin resistance and the development of hepatic steatosis. To characterize the molecular changes that promote hepatic steatosis, transcriptomics, proteomics, and metabolomics technologies were applied to liver samples from C57BL/6J mice obtained from two independent intervention trials. After 12 wk of high-fat feeding the animals became obese, hyperglycemic, and insulin resistant, had elevated levels of blood cholesterol and VLDL, and developed hepatic steatosis. Nutrigenomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 48 publications
4
54
2
Order By: Relevance
“…Notably, in these 2 studies, weight gain did not increase beyond that of the control. On the other hand, 2 similar studies of longer duration reported MAT1a upregulation (41,42) concomitant with increased fat gain. Zucker fatty rats, in which a leptin receptor mutation produces hyperphagia and obesity, have increased hepatic SAM (43).…”
Section: Discussionmentioning
confidence: 85%
“…Notably, in these 2 studies, weight gain did not increase beyond that of the control. On the other hand, 2 similar studies of longer duration reported MAT1a upregulation (41,42) concomitant with increased fat gain. Zucker fatty rats, in which a leptin receptor mutation produces hyperphagia and obesity, have increased hepatic SAM (43).…”
Section: Discussionmentioning
confidence: 85%
“…Metabolomics is powerful in that it provides unbiased datasets which can be analysed to infer mechanistic information [25,26]. For example, metabolomic studies of liver from mice or rats subjected to an HFD have demonstrated significant diet induced changes in lysolipids, choline, fatty acids and associated intermediates and amino acids [2729]. The global summary of the present analysis indicated that 48 of 341 metabolites were significantly elevated in liver of AdKO mice after 6 weeks of HFD, whereas 99 were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were treated according to the manufacturer's instructions and analyzed via LC-MS/MS (3200QTRAP LC/MS/MS, Applied Biosystems). Spectra were processed using the Analyst ® 1.5 Software [27]. HPLC-MS/MS detection of hepatic SAM and SAH levels was performed using a Waters 2795 alliance HT, coupled to a Quattro Micro API tandem mass spectrometer (Waters Corporation) according to the previously described methodology with minor modifications [28].…”
Section: Methodsmentioning
confidence: 99%